THE EFFECT OF COMPANY SIZE, PROFITABILITY AND SOLVENCY ON AUDIT DELAY (EMPIRICAL STUDY OF CONSUMER GOODS INDUSTRY SECTOR COMPANIES LISTED ON THE STOCK EXCHANGE INDONESIA) - Tanel, Jesica; Daryatno, Andreas Bambang (International Journal of Application on Economics and Business, 2024)
The purpose of this study is to examine how firm size, profitability, and solvency affect audit delay. The dependent variable is audit delay, while the independent variables are company size (X1), profitability (X2), and solvency (X3). Purposive sampling was used to choose the research sample, which consisted of companies in the consumer products sector that were listed on the Indonesia Stock Exchange. The findings demonstrated that a firm's size significantly influences the risk of an audit delay, with a larger company having a higher chance of a delay. This result is in line with earlier studies that show a connection between audit delay and company size. It has also been demonstrated that profitability significantly affects audit delay. High profitability businesses typically have shorter audit delays, suggesting that a company's capacity to turn a profit might have an impact on how quickly financial information is provided. This study strengthens earlier research demonstrating a connection between audit delay and profitability.